Levels of potential bioactive compounds including carotenoids, vitamin C and phenolic compounds, and expression of their cognate biosynthetic genes vary significantly in different varieties of potato (Solanum tuberosum L.) grown under uniform cultural conditions. (27th April 2015) - Valcarcel, Jesus; Reilly, Kim; Gaffney, Michael; O'Brien, Nora M
Abstract: BACKGROUND: In addition to their high carbohydrate content, potatoes are also an important dietary source of vitamin C and bioactive secondary metabolites, including phenolic compounds and carotenoids, which have been suggested to play a role in human health. The expression of genes encoding key enzymes involved in the synthesis of these compounds was assessed by reverse transcription–quantitative polymerase chain reaction and compared to the accumulation of the corresponding product in seven potato varieties showing contrasting levels of metabolite accumulation. RESULTS: Strong positive correlations were found between phenolic content in the flesh of tubers and transcript levels of phenylalanine ammonia lyase (PAL) and chalcone synthase (CHS) genes. The expression of PAL and CHS was also related to that of AN1, a transcription factor involved in the synthesis of anthocyanins, suggesting that these genes are regulated in a coordinated manner. No clear relationship was found between transcript levels of phytoene synthase (PSY) orl ‐galactono‐1, 4‐lactone dehydrogenase (GLDH) genes and total carotenoid or vitamin C accumulation, respectively. CONCLUSION: Data indicate that levels of total phenolic and flavonoid compounds in potato are controlled primarily by PAL and CHS gene expression. Transcript levels of PSY and GLDH did not control accumulation of carotenoids or vitamin C. © 2015 Society of Chemical Industry